Effect of Multi-Ingredient Preworkout Supplementation on Repeated Sprint Performance in Recreationally Active Men and Women. Issue 4 (April 2020) - Gonzalez, Adam M.; Pinzone, Anthony G.; Bram, Jonathan; Salisbury, Jillian L.; Lee, Sean; Mangine, Gerald T.
Abstract : Abstract: Gonzalez, AM, Pinzone, AG, Bram, J, Salisbury, JL, Lee, S, and Mangine, GT. Effect of multi-ingredient preworkout supplementation on repeated sprint performance in recreationally active men and women. J Strength Cond Res 34(4): 918–923, 2020—The purpose of this investigation was to examine the effects of acute supplementation of a multi-ingredient preworkout supplement (MIPS), containing a proprietary blend of ancient peat and apple extracts, creatine monohydrate, taurine, ribose, and magnesium, on sprint cycling performance. Seventeen recreationally active men and women (23.2 ± 5.9 years; 172.9 ± 14.3 cm; 82.4 ± 14.5 kg) underwent 2 testing sessions administered in a randomized, counterbalanced, double-blind fashion. Subjects were provided either MIPS or placebo (PL) one hour before performing a sprint cycling protocol, which consisted of ten 5-second "all-out" sprints interspersed by 55 seconds of unloaded pedaling. Average power (PAVG ), peak power (PPK ), average velocity (VAVG ), and distance covered were recorded for each sprint. Separate linear mixed models revealed decrements ( p < 0.05) compared to the first sprint in PAVG (75–229 W) and PPK (79–209 W) throughout all consecutive sprints after the initial sprint during PL. Likewise, diminished ( p ⩽ 0.029) VAVG (3.37–6.36 m·s −1 ) and distance covered (7.77–9.00 m) were noted after the third and fifth sprints, respectively, during PL. By contrast, during MIPS, only VAVG decreased (2.34–5.87 m·s −1, p ⩽ 0.002) on consecutive sprints after the first sprint, whereas PAVG and PPK were maintained. In addition, a significant decrease ( p = 0.045) in distance covered was only observed on the ninth sprint during MIPS. These data suggest that recreational athletes who consumed the MIPS formulation, one hour before a repeated sprinting session on a cycle ergometer, better maintained performance compared with PL.